The Structures of Political, Economic, and Socio-cultural Rhetorical Narratives on Social Media - Samuel Gunawan; Theopilus Joko Riyanto; Liem Satya Limanta (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This research was conducted on the ground of the reason for the increasingly widespread use of narratives on various social media platforms. Narrative is an event whereby someone represents an event aiming to influence the understanding, emotions and values of others. This study qualitatively aims to capture the most common elements of narrative structure focusing on political, economic, and socio-cultural rhetorical narratives data originated from social media platforms. The theoretical model of narrative structure consisting of Abstract, Orientation, Complicating Actions, Resolution, Evaluation and Coda, as proposed by Labov and Waletzky was used to analyze the narrative data collected during the first four months of 2022. On the ground of social situated meanings, the findings show that the most common model of narrative structure is fully used whenever greater details of events, facts, or information are needed to be emphasized. For such reasons, all the elements of narrative structure are held to be obligatory. The findings show that some elements of narrative structure are left out and held to be optional as such elements are not considered necessary to convey the main content. In addition, the findings also show that some particular element allows it to be further developed with more embedded events, facts, opinion, or information.